IMPLICATION OF FLOWER COLORS TO HUMAN BEINGS AND INSECTS - Iyengar, Shamanta (International Journal of Research -GRANTHAALAYAH, 2014)
Flowers owe their beauty to their infinite range of shapes and colours and are symbolized with spiritualism and expression, conveyance of sentiments of human beings. On the other hand plants employ flowers to form association with animals to ensure pollination across multi –generation. To achieve this they provide clues and positive enforcements. The diversification in flower colours and other attributes has matched in nature with co-evolution of abundant species of insects. This paper deals with the perception of flower colours by insects and also their denotions to human beings.